Annual variation of the landscape pattern in the Liao River Delta wetland from 1976 to 2020. (1st June 2022) - Chen, Kexin; Cong, Pifu; Qu, Limei; Liang, Shuxiu; Sun, Zhaochen
Abstract: The Liao River Delta wetland is an important breeding base for rare waterbirds in the world. In recent years, with the immense disturbance of human activities, the wetland has degraded. It is a prerequisite for wetland conservation and restoration to accurately extract and monitor changes in wetland area and spatial distribution. Here, based on Landsat time-series images from 1976 to 2020 in the Liao River Delta wetland, we used a synthesized upon object-oriented classification and hierarchical classification method to detect the wetland changes. We analyzed the driving factors of these change. The study found that the total wetland area have reduced by 188.00 km 2 by human activities during the 45 years, among which the decrease was the most drastic from 2009 to 2012. Natural wetland area have decreased by 414.90 km 2, with a large reduction in intertidal muds, mainly due to the increase in human activities after the establishment of the city in 1984. Human-made wetland area have increased by 226.90 km 2, mainly influenced by changes in the transfer of intertidal muds to aquaculture ponds and paddy fields. A significant increase in the area of construction land among non-wetlands, mainly caused by the completion of Panjin New Port in 2009. Human activities were the main factors causing the extravagant changes in the Liao River Delta wetland.